Tricopter Vehicle Frame Structure Design Integrated as Platform of Fixed Wing Atha Mapper 2150 - Kaspul Anuar; Warman Fatra; Musthafa Akbar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
To upgrade aerial vehicle of Atha Mapper 2150 capable of vertical take-off and landing capability, it needs to be integrated to the tricopter vehicle. In this study the tricopter frame structure was designed based on the Atha Mapper 2150 fixed wing vehicle. This study began with a calculation process to determine the dimensions of the tricopter.. Next, the process of building four tricopter concept designs with variations of the shape of the frame and the cross section of the arm. The four concept designs are selected using a decision matrix. Based on the values in decision matrix table, the design concept I (Y configuration and rectangular arm cross section) was the best design, because it has the highest weighting value. The selected design was then simulated for its structural strength in Ansys software by giving a load of thrust to the three arms of the tricopter frame. In the middle of frame is given a boundary condition in the form of hinges. From the static simulation results of the tricopter frame structure, the maximum stress value was 54,126 MPa, which occurred on the M3 arm. The greatest total deformation also occurred in the M3 arm with a value of 10,335 mm. The safety factor value of tricopter frame structure was 8.77. This shows the tricopter frame structure with the main material in the form of carbon fiber, acrylic and PLA meets the required safety criteria.